Effect of Modification on Characteristic Values of TDA Curves - Gumienny, Grzegorz; Szymczak, Tomasz; Pacyniak, Tadeusz (My University, 2014)
The work presents the examination results of the effect of strontium and antimony modification on the microstructure of a cast and the characteristic values of the TDA curves. Strontium and antimony modifiers were added to silumin 226 in a melting crucible furnace, separately, in the amounts of 0.1; 0.2 and 0.3% of the mass of the modified metal. After modification, the silumin was refined with the solid refiner ECOSAL-Al 113 in the amount of 0.5% of the charge mass.
Keywords: Theoretical basics of casting processes; Silumin 226; Modification; proces odlewania; podstawy teoretyczne; silumin 226; modyfikacje